Benign adenoidal hypertrophy caused by adenovirus presenting as a nasopharyngeal mass concerning for malignancy. (November 2020) - Nicodemo, J.; Hamersley, E.; Baker, P.; Reed, S.
Abstract: Benign adenoidal hypertrophy is the most common cause of nasopharyngeal obstruction. However, depending on size and location, masses may cause nasopharyngeal obstruction. We present our experiences with a ten-year-old female who presented with what appeared to be a large nasopharyngeal mass that was initially favored to be malignant and was ultimately found to be adenoid hypertrophy related to acute infection with adenovirus.